Short-Term Outcomes of Management of Endovascular Aneurysm Repair in Patients With Dilated Iliacs. (April 2015) - Stather, P. W.; Rhema, I. A.; Sidloff, D. A.; Sayers, R. D.; Bown, M. J.; Choke, E.
Objectives: This study aims to evaluate outcomes following endovascular aneurysm repair (EVAR) in patients with dilated but not aneurysmal common iliac arteries. Methods: Data prospectively collected from 342 elective EVARs were analyzed retrospectively. Dilated common iliac anatomy was defined as 21 to 24 mm. Patients with iliac aneurysms or external iliac artery (EIA) extension were excluded. Patients were followed up using clinical review, plain radiographs, duplex imaging, and selective computed tomography scanning. Results: Median age was 75 years with a mean follow-up of 3.6 years. In all, 33 patients had dilated common iliac arteries (DCIAs) and 309 had non-dilated common iliac arteries (NDCIA). There was no difference in aneurysm diameter or neck characteristics (length, diameter, angulation, thrombus, and flare) between the subgroups. There was no significant difference in technical success, 30-day mortality, late mortality, aneurysm-related mortality, 30-day reinterventions, stent graft migration, limb occlusion, sac expansion, graft rupture, type 1 endoleaks, type 3 endoleaks, and total reinterventions (all P s > .05). There was a significant decrease in type II endoleaks in patients with DCIA compared to NDCIA (NDCIA 12.9% and DCIA 0.0%; P = .02). Conclusion: Patients presenting with abdominal aortic aneurysms with DCIA can be successfully treated with EVAR with no increase in complications without extension into the EIA.